PENGARUH AI (ARTIFICIAL INTELLIGENCE) TERHADAP LITERASI DIGITAL DAN KETERAMPILAN ABAD 21 - Putri Maharani, Salsa; Fathiyah Salsabilah; Nur Artika Sari; Ghefira Rhoudhotul Janah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) technology has brought about significant changes in the world of education, particularly in enhancing digital capabilities and the skills needed in the 21st century. AI is not only used as a learning aid but also influences how students access, process, and use information digitally. However, despite the various opportunities it offers, the use of AI also brings challenges that need to be carefully examined and considered. Therefore, this article seeks to analyze the impact of AI use on digital literacy and the skills needed in the 21st century, as well as identifying the challenges that arise in this regard. This research uses a literature study method by examining various relevant and recent books and scientific articles. Research shows that AI helps improve digital literacy skills, for example in searching for information, understanding technology, and managing digital information better. Furthermore, AI also helps improve 21st-century skills such as critical thinking, creativity, communication skills, and collaboration. However, the main challenges faced include over-reliance on AI, poor ability to disseminate digital information, and issues of ethics and academic integrity. Based on these findings, it can be concluded that the use of AI in education must be accompanied by increased digital literacy, learning guidance, and ethical awareness. This is essential for AI to become a truly effective and continuously evolving learning tool.